1997
DOI: 10.1071/r97002
|View full text |Cite
|
Sign up to set email alerts
|

Physiological limits to further improvement in the efficiency of oestrous synchronization in goats

Abstract: The variability between animals in the timing of oestrus after administration of a synchronization treatment seems to explain the low rate of fertility in goats inseminated at a predetermined time after progesterone withdrawal. Two experiments were performed during the breeding season to test whether the variation was due to the exogenous hormone regime or to the endogenous physiology of the animals. Twenty-one goats were given a synchronization treatment consisting of a vaginal sponge impregnated with 45 mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…We confirmed the variability of the onset of estrus in dairy goats after synchronization with a progestagen/eCG treatment already described in other studies [2,4,13,19,22]. The variability of the onset of estrus and LH peak increased significantly with the repetition of treatments (Tabs.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We confirmed the variability of the onset of estrus in dairy goats after synchronization with a progestagen/eCG treatment already described in other studies [2,4,13,19,22]. The variability of the onset of estrus and LH peak increased significantly with the repetition of treatments (Tabs.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, we also suggest that the management of reproduction could introduce some genetic variability between the herds: AI was regularly used in H1 with subsequent introduction of new genotypes while H2 was in-bred. So, this herd effect could constitute a part of the endogenous physiology of the animals suggested by Freitas et al [13] to explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Onset of oestrus to LH peak and LH peak to ovulation intervals The onset of oestrus to LH peak interval observed in oestrus synchronized with prostaglandins (12.8 6 1.1 h) was similar to that observed by Freitas et al (1997a) in oestrus synchronized with FGA (12.0 6 4.4 h). In both studies, no differences were found between induced and natural oestrus regarding the onset of oestrus to LH peak interval.…”
Section: Discussionmentioning
confidence: 50%
“…Synchronization of oestrus is important in the improvement of reproductive efficiencies and management processes (Al‐Merestani et al 1999). Two types of intravaginal sponges are being used for oestrous synchronization of does, namely medroxyprogesterone acetate (MAP) (Menegatos et al 1995) and flugestone acetate (FGA) (Freitas et al 1997). Pregnant mare serum gonadotrophin (PMSG) was injected with the sponge treatment to improve fecundity (Baril et al 1998).…”
Section: Introductionmentioning
confidence: 99%